La leucina en el desempeño deportivo: ejercicios aeróbicos y anaeróbicos (2017)
Leucine is an amino acid used by cells for protein synthesis, plays an important role in athletes' physical performance, in the degradation of muscle tissue by natural aging and muscular anabolism, therefore, it is important to know the main differences intheir use as a dietary supplement in aerobic and anaerobic exercises, as these demand a muscular development and a different energy supply by the energy systems. Differences in muscle synthesis were identified in aerobic and anaerobic exercises with a leucine-rich diet, the impact on muscle performance after a leucine intake, the human body's limit on leucine metabolism and the adverse effects of an intake of the above-mentioned amino acid. A number of investigative articles were collected to identify this information and the results were analyzed and compared. It was concluded that leucine, as an essential amino acid, must be supplied through the diet and its consumption should be parallel to a high protein diet. Leucine offers slight improvements in sports performance, but it helps in recovery after intense exercise where there is muscle damage, possibly limiting its effectiveness as ergogenic aid, and therefore, its main application lies in the treatment of type 2 diabetes and sarcopenia. Leucine has no adverse effects on its use, but a maximum dose of 550mg/kg daily is recommended, mainly as a preventive measure in the absence of long-term studies of exposure to leucine at high concentrations.